Babel's Tower translated : Genesis 11 and ancient Jewish interpretation - Sherman, Phillip Michael. (Biblical Interpretation Series, 2013)
In Babel's Tower Translated , Phillip Sherman explores the narrative of Genesis 11 and its reception and interpretation in several Second Temple and Early Rabbinic texts (e.g., Jubilees, Philo, Genesis Rabbah). The account of the Tower of Babel (Genesis 11:1-9) is famously ambiguous. The meaning of the narrative and the actions of both the human characters and the Israelite deity defy any easy explanation. This work explores how changing historical and hermeneutical realities altered and shifted the meaning of the text in Jewish antiquity.